(untitled) (Research, Society and Development, 2025)
The general objective is to investigate how the application of the SELF Matrix can promote the entrepreneur’s self-awareness, influence strategic decision-making, and contribute to business sustainability. Social research was conducted through interviews and questionnaires with entrepreneurs, Business success depends on multiple factors, including management skills, strategic planning, and emotional competencies. However, many entrepreneurs face challenges that go beyond technical issues, often influenced by emotional inversion and internal censorship processes. This study explores the application of the SELF Matrix as a tool for analysis and self-awareness, enabling entrepreneurs to better understand their limitations and strengths. The research is based on Keppe’s Theory and uses qualitative methodologies to assess how self-awareness can impact decision-making and reduce the business failure rate.